Differential Pharmacologic Properties of the Two C75 Enantiomers: (+)‐C75 Is a Strong Anorectic Drug; (−)‐C75 Has Antitumor Activity. Issue 5 (26th April 2013) - Makowski, Kamil; Mera, Paula; Paredes, David; Herrero, Laura; Ariza, Xavier; Asins, Guillermina; Hegardt, Fausto G.; García, Jordi; Serra, Dolors
ABSTRACT C75 is a synthetic compound described as having antitumoral properties. It produces hypophagia and weight loss in rodents, limiting its use in cancer therapy but identifying it as a potential anti‐obesity drug. C75 is a fatty acid synthase (FAS) inhibitor and, through its coenzyme A (CoA) derivative, it acts as a carnitine palmitoyltransferase (CPT) 1 inhibitor. Racemic mixtures of C75 have been used in all the previous studies; however, the potential different biological activities of C75 enantiomers have not been examined yet. To address this question we synthesized the two C75 enantiomers separately. Our results showed that (−)‐C75 inhibits FAS activity in vitro and has a cytotoxic effect on tumor cell lines, without affecting food consumption. (+)‐C75 inhibits CPT1 and its administration produces anorexia, suggesting that central inhibition of CPT1 is essential for the anorectic effect of C75. The differential activity of C75 enantiomers may lead to the development of potential new specific drugs for cancer and obesity. Chirality 25:281–287, 2013. © 2013 Wiley Periodicals, Inc.